Temperature dependent percolation mechanism for conductivity in TiO3 revealed by a microstructure study - R German; B Zimmer; T C Koethe; A Barinov; A C Komarek; M Braden; F Parmigiani; P H M van Loosdrecht (Materials Research Express, 2018)
We have performed optical microscopy, micro-photoelectron spectroscopy, and micro-Raman scattering measurements on ${{\rm{Y}}}_{0.63}$ ${Ca}_{0.37}$ TiO _3 single crystals in order to clarify the interplay between the microstructure and the temperature dependent electronic transport mechanisms in this material. Optical microscopy observations reveal dark and bright domain patterns on the surface with length scales of the order of several to a hundred micrometers showing a pronounced temperature dependent evolution. Spatially resolved photoelectron spectroscopy measurements show the different electronic character of these domains. Using micro-Raman spectroscopy, we observe a distinct temperature dependence of the crystal structure of these domains. On the basis of these findings the different domains are assigned to insulating and metallic volume fractions, respectively. By decreasing the temperature, the volume fraction of the conducting domains increases, hence allowing the electrons to percolate through the sample at temperatures lower than ∼150 K.